Hubungan Kadar Timbal Dalam Darah dengan Kadar Hemoglobin pada Operator SPBU Gombel Semarang: The Correlation of Lead Level in the Blood with Hemoglobin Level on the Operator of Public Refueling Station in Gombel Semarang - Susiani, Susiani; Lestari, Mastuti Widi (Jurnal Surya Medika (JSM), 2022)
Lead is a heavy metal that is added in the manufacture of gasoline. Lead acts as an anti-knock to increase engine efficiency. Lead can cause air pollution. The main sources of lead pollution are motor vehicle fumes and gasoline fumes. Operator of Public Refueling Station are workers at high risk of being exposed to lead. The continuous accumulation of lead can inhibit the formation of hemoglobin. Research is needed to know the relationship between lead level in blood and hemoglobin level on the Operator of Public Refueling Station in Gombel Semarang. The research type is observational descriptive analytic with a cross sectional design. The research sample of 18 respondents is the entire population of Operator of Public Refueling Station in Gombel Semarang. Lead level in blood is an independent variable. Hemoglobin level is the dependent variable. Lead levels were measured by the ICP-MS method and using the Agilent 7700 X. Hemoglobin levels were measured by the SLS-Hemoglobin Method and using the Sysmex XN 1000. The research result was lead level in blood 1,6-5,7 μg/dL, hemoglobin level 12,4-18,1 g/dL. Test result of Spearman correlation obtained p= 0,581 ; r=-0,139. It was concluded that there was no significant correlation between the level of blood lead and level of hemoglobin on Operator of Public Refueling Station in Gombel Semarang.